The Role of Value Judgment in Congruent Personalities, Trait Authenticity, and Authentic Leadership - Malcolm North; Julie Nelson; Clifford Hurst (Journal of Scholarly Engagement)
Research in value-behavior relations has yet to explore the role of value judgment in predicting authentic trait and behaviors. This study explored how individual value orientation and judgment relate to psychological maturity in the development of an authentic and congruent personality. A regression analysis with 346 working professionals examined if value judgment predicts psychological congruence and authenticity in personal and professional contexts. In addition, the relationship between value judgment and trait authenticity in 157 working adults and 83 supervisors from education, health, and non-profit organizations in the U.S was explored. Value judgment was measured by two profiles of the Hartman Value Profile (HVP), a judgment profiling instrument delineating the thinking, evaluation, problem-solving patterns, and orientation in 52 indices in personal (HVPII) and social domains (HVPI). Trait authenticity was measured with the Authenticity Scale (AS) comprising of three subscales measuring authentic living, self-alienation, and capacity to resist external influence. Support was found for all hypotheses testing for associations between value judgment and authenticity, and if value judgment predicted psychological congruence and authentic leadership and further identifies the type of value judgment used in the constructs of congruence and authenticity.